Предмет: Алгебра,
автор: 16polichka08
(2х-1)^4+(2х-1)^2-2=0
Ответы
Автор ответа:
1
Ответ:
х = 1
Объяснение:
(2х-1)⁴+(2х-1)²-2 = 0
Пусть (2х-1)² = y, y≥0, тогда
у²+у-2 = 0
D = 1²-4*(-2) = 1+8 = 9 = 3²
y1 = (-1+3)/(2*1) = 2/2 = 1
y2 = (-1-3)/(2*1) = -4/2 = -2 - не подходит по условию
Вернёмся к замене
Если у = 1,то
2х-1 = 1
2х = 1+1
2х = 2
х = 1
Похожие вопросы
Предмет: Русский язык,
автор: netans
Предмет: Русский язык,
автор: Denissspo
Предмет: Русский язык,
автор: 2005150
Предмет: Русский язык,
автор: danila15427
Предмет: Беларуская мова,
автор: 07701gale